Conditions, methods and principles of healthcare system records integration – part 2 - Nyczaj, Krzysztof (Polish Journal of Public Health, 2009)
The article is a continuation of the author’s reflections on the conditions and the role of registries in shaping corporate information in health care, published in the previous issue of “Public Health”, in which he pointed to the shortcomings of the current definition of a public register and attempted to organize the terminology, with particular emphasis on distinguishing types of data sets such as the administrative record, records, list. In this article the author attempts to develop a classification of health care records, by using the achievements of the recognized in literature authors, then, on the basis of own experience and expertise, assign to separate classes – the self-identified data sets. Author also proposes to develop a hierarchical model for health care records, showing the desired information and the hierarchical relationship between different types of data sets in healthcare.